ENVIRONMENTAL IMPACT OF MEDICAL SERVICES AND POPULATION HEALTH IN NAMANGAN CITY AREAS - Yusupov Khasanboy Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the impact of medical services in the area of Namangan city and the impact of city development on the environment is studied. Issues of reducing the impact on the health of the population through the development of the green economy of cities are covered.